Streaming Uniformity and Language Diversity on Netflix and Prime Video Streaming Platforms - Florea, Silvia (Historia y Comunicación Social, 2026)
Mediated entertainment plays a crucial role in influencing the language exposure of Europeans. While the widespread use of English in streaming platforms enhances engagement, it jeopardizes linguistic diversity, marginalizing minority languages and obstructing mutual comprehension. This study takes a methodological approach to examine linguistic diversity on the Netflix and Prime Video streaming platforms from a twofold perspective: the predominance of English over other official languages in Europe, and the perspective of minority or minoritized languages lacking official recognition within the European Union yet serving as the primary language for large populations. By combining quantitative data on catalogue-level availability, targeted user interface audits, and qualitative assessments of audiovisual translation quality, the study seeks to identify the mechanisms through which minoritized languages are currently marginalized in digital media environments.
Keywords: mediated entertainment; streaming platforms; English; minoritized languages; diversity; hegemony